Clinical, ocular motor, and imaging profile of Niemann-Pick type C heterozygosity. (21st April 2020) - Bremova-Ertl, Tatiana; Sztatecsny, Clara; Brendel, Matthias; Moser, Marlene; Möller, Bettina; Clevert, Dirk A.; Beck-Wödl, Stefanie; Kun-Rodrigues, Celia; Bras, Jose; Rominger, Axel; Ninov, Dimitar; Strupp, Michael; et al.
Abstract : Objective: To characterize subclinical abnormalities in asymptomatic heterozygote NPC1 mutation carriers as markers of neurodegeneration. Methods: Motor function, cognition, mood, sleep, and smell function were assessed in 20 first-degree heterozygous relatives of patients with Niemann-Pick disease type C (NPC) (13 male, age 52.7 ± 9.9 years). Video-oculography and abdominal ultrasound with volumetry were performed to assess oculomotor function and size of liver and spleen. NPC biomarkers in blood were analyzed. 18 F-fluorodesoxyglucose PET was performed (n = 16) to detect patterns of brain hypometabolism. Results: NPC heterozygotes recapitulated characteristic features of symptomatic NPC disease and demonstrated the oculomotor abnormalities typical of NPC. Hepatosplenomegaly (71%) and increased cholestantriol (33%) and plasma chitotriosidase (17%) levels were present. The patients also showed signs seen in other neurodegenerative diseases, including hyposmia (20%) or pathologic screening for REM sleep behavior disorder (24%). Cognitive function was frequently impaired, especially affecting visuoconstructive function, verbal fluency, and executive function. PET imaging revealed significantly decreased glucose metabolic rates in 50% of participants, affecting cerebellar, anterior cingulate, parieto-occipital, and temporal regions, including 1 with bilateral abnormalities. Conclusion: NPC heterozygosity, which has a carrier frequency of 1:200 in the general population, is associated with abnormal brain metabolism and functional consequences. Clinically silent heterozygous gene variations in NPC1 may be a risk factor for late-onset neurodegeneration, similar to the concept of heterozygous GBA mutations underlying Parkinson disease.